Toxic algae and other marine biota: detection, mitigation, prevention and effects on the food industry - McCollough, Bianca (Kansas State University, 2016)
Harmful Algal Blooms (HABs) including Cyanobacteria and other toxic marine biota are responsible for similar harmful effects on human health, food safety, ecosystem maintenance, economic losses and liability issues for aquaculture farms as well as the food industry. Detection, monitoring and mitigation are all key factors in decreasing the deleterious effects of these toxic algal blooms. Harmful algal blooms can manifest toxic effects on a number of facets of animal physiology, elicit noxious taste and odor events and cause mass fish as well as animal kills. Such blooms can adversely impact the perception of the efficacy and safety of the food industry, water utilities, the quality of aquaculture and land farming products, as well as cause ripple effects experienced by coastal communities. HABs can adversely impact coastal areas and other areas reliant on local aquatic ecosystems through the loss of revenues experienced by local restaurants, food manufacturers as well as seafood harvesting/processing plants; loss of tourism revenue, decreased property values and a fundamental shift in the lives of those that are reliant upon those industries for their quality of life. This paper discusses Cyanobacteria, macroalgae, HABs, Cyanobacteria toxins, mitigation of HAB populations and their products as well as the ramifications this burgeoning threat to aquatic/ landlocked communities including challenges these toxic algae pose to the field of food science and the economy.
Keywords: Algal Toxin; Food Protection; Cyanotoxin; Domoic AcidCyanobacteria